Patients' Perceptions of Interprofessional Collaboration: A Scoping Review - Robynne Gilchrist; Aayesha Kholvadia; William (Bill) (The Beryl Institute, 2024)
Collaboration has emerged as a pivotal element within an intentional person-centred healthcare framework. However, there is a need for evaluative feedback from patients to enhance interprofessional collaboration and its outcomes. The objective of this review was to describe the state of knowledge on the perspectives of patients living with a chronic condition regarding their experiences of interprofessional collaboration. A scoping review across five online databases (EBSCOhost, Google Scholar, PubMed Central, ScienceDirect, and Taylor & Francis Online; February 2023) identified all peer-reviewed literature published in English between the years 2018 and 2023 that reported on patients' perspectives of, and experiences with, interprofessional collaboration and/or its effect on patient care and outcomes. Articles selected for final appraisal were descriptively and thematically analysed. The literature search yielded 3454 articles. One hundred and four (104) full-text articles were included for appraisal based on the eligibility criteria. Once study selection and critical appraisal were completed, 25 studies were included in the review. Three themes were reported on the patient's perspective of interprofessional collaboration: (i) Team functioning, (ii) Patient involvement, and (iii) Coordinated care. Interprofessional relations, role clarification, and team-based communication were the main factors essential to successful team functioning as perceived by patients. Further exploration of these key factors is necessary to guide the development of improvement strategies or interventions focused on strengthening interprofessional collaboration and the patient's experience. The patient's perspective of interprofessional collaboration still warrants further investigation to improve patient experience, quality of care, and outcomes in a collaborative environment.